2010
DOI: 10.1021/jm100608j
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Dependent Protein Kinase (DNA-PK) Inhibitors. Synthesis and Biological Activity of Quinolin-4-one and Pyridopyrimidin-4-one Surrogates for the Chromen-4-one Chemotype

Abstract: Following the discovery of dibenzo[b,d]thiophen-4-yl)-2-morpholino-4H-chromen-4-one (NU7441) ( Leahy , J. J. J. ; Golding , B. T. ; Griffin , R. J. ; Hardcastle , I. R. ; Richardson , C. ; Rigoreau , L. ; Smith , G. C. M. Bioorg. Med. Chem. Lett. 2004 , 14 , 6083 - 6087) as a potent inhibitor (IC₅₀ = 30 nM) of DNA-dependent protein kinase (DNA-PK), we have investigated analogues in which the chromen-4-one core template has been replaced by aza-heterocyclic systems: 9-substituted 2-morpholin-4-ylpyrido[1,2-a]py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Replacement of the chromen-4-one scaffold by the isosteric pyrimidoisoquinolinone structure gave equipotent compounds (8; IC 50 =0.28 µM) [22]. Multiple studies have revealed that 6 acts in vitro as a radiosensitiser, [23] and as a chemo-potentiator of topoisomerase II (TOP2) poisons in human leukaemia cell lines [24].…”
Section: Chromen-4-ones and Surrogates: Ly2094002 And Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacement of the chromen-4-one scaffold by the isosteric pyrimidoisoquinolinone structure gave equipotent compounds (8; IC 50 =0.28 µM) [22]. Multiple studies have revealed that 6 acts in vitro as a radiosensitiser, [23] and as a chemo-potentiator of topoisomerase II (TOP2) poisons in human leukaemia cell lines [24].…”
Section: Chromen-4-ones and Surrogates: Ly2094002 And Derivativesmentioning
confidence: 99%
“…VX-984 (22), disclosed by Vertex Pharmaceuticals, is a DNA-PK inhibitor currently undergoing a phase I clinical study, in combination with pegylated liposomal doxorubicin in patients with advanced solid tumours or lymphomas. Compound 22 has an IC 50 of 88 ± 64 nM for inhibition of DNA-PKcs autophosphorylation (Ser2056) in A549 lung cancer cells, with good selectivity versus other PI3K family members [40] …”
Section: Vx-984mentioning
confidence: 99%
“…It is well established that genetic deficiency or inhibition of DNA-PK results in radiosensitivity of oxygenated cells [18,19,[36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…These data support the possibility that NU7441 is an effective SMI of DNA-PK and in combination treatment with current chemotherapeutic regimens, such as IR or etoposide treatment, a decrease in repair would result in an increase in treatment efficacy. Continued development of both classes of inhibitors including NU7613 continue to target the ATP binding pocket of DNA-PK and result in increased potency and selectivity while also increasing cellular activity (Clapham et al, 2011;Cano et al, 2010;sage-El et al, 2008;Hollick et al, 2007;Griffin et al, 2005), however, their true utility as therapeutic agents awaits clinical assessment.…”
Section: Dna-pk Inhibitors -Targeting Non-homologous End Joining Doubmentioning
confidence: 99%